Tanggung Jawab Hukum bagi Konsumen atas Kerugian Layanan GrabFood oleh PT. Grab Teknologi Indonesia - Mirena, Soya Putri; Haryanto, Imam (Universitas Semarang, 2024)
The purpose of this research is to study the legal protection of the application of food messaging services in Indonesia and the legal responsibility of PT Grab for consumer losses associated with the rules of cooperation between PT Grab and the seller and driver. The services provided by PT Grab in its GrabFood feature activities must refer to Article 4 of Law No. 8 of 1999 in order to protect consumer rights. There are many cases of losses experienced by consumers such as orders that have been paid for not being delivered or discrepancies in goods with their orders where there are defaults made by the seller. So, consumer protection against online buying and selling is an important concern. This research uses a normative jurisprudence method, a technique commonly used in legal research to analyze legal issues with reference to applicable regulations. This research is studied with a broad discussion related to problems that harm consumers of services from PT Grab, especially GrabFood, such as price discrepancies and poor food quality not only related to product halalness. Consumer protection is an important aspect of the food delivery service business such as GrabFood. PT. Grab is responsible for problems related to the use of its application which creates a relationship between transportation service providers and consumers, the driver is a possible party to be held accountable to the transportation provider because the driver was given the trust to buy food on the GrabFood service. and in the event of food discrepancies related to quality and quality which can even harm consumers, it is the responsibility of the restaurant owner. Tujuan penelitian ini unatuk mengkaji perlindungan hukum aplikasi layanan pesan antar makanan di Indonesia dan tanggung jawab hukum PT. Grab terhadap kerugian konsumen dikaitkan dengan aturan kerjasama antara PT. Grab dengan pihak penjual dan driver. Layanan yang telah disediakan PT.Grab dalam kegiatannya fitur GrabFood harus mengacukan atas Pasal 4 Undang-Undang No 8 Tahun 1999 supaya melindungi hak pembeli. Terdapat banyaknya kasus kerugian yang dialami konsumen seperti pesanan yang sudah dibayar tidak kunjung dikirim atau ketidaksesuaian barang dengan pesanannya yang mana terdapat wanprestasi yang dilakukan pihak penjual. Maka, perlindungan konsumen terhadap jual beli online ini jadi perhatian penting. Penelitian ini menggunakan metode yuridis normatif, yaitu teknik yang biasa digunakan di penelitiannya hukum untuk menganalisis permasalahan hukum dengan mengacu pada peraturan yang berlaku. Penelitian ini dikaji dengan pembahasannya meluas terkait masalah-masalah yang merugikan konsumen layanan dari PT. Grab khususnya GrabFood, seperti ketidaksesuaian harga dan kualitas makanan yang buruk tidak hanya terkait kehalalan produk. Perlindungan konsumen merupakan aspek penting di bisnis layanan pengiriman makanan seperti GrabFood. PT. Grab bertanggung jawab dalam masalah terkait penggunaan aplikasinya yang menciptakan hubungan penyedia jasa transportasi dan konsumen, Pihak driver sebagai pihak yang memungkinkan untuk diminta pertanggungjawaban terkait penyelenggara angkutan karena driver telaah diberi kepercayaan untuk membelikan makanan pada layanan GrabFood. dan dalam hal ketidaksesuaian makanan terkait kualitas dan mutunya yang bahkan dapat merugikan konsumen, maka menjadi tanggung jawab pemilik resto.